Performance evaluation of feature sets for carried object detection in still images - Kulkarni, Hrushikesh N., author; Beveridge, J. Ross, advisor; Draper, Bruce A., advisor; Pasricha, Sudeep, committee member; Alciatore, David G., committee member (Colorado State University. Libraries, 2014)
Human activity recognition has gathered a lot of interest. The ability to accurately detect carried objects on human beings will directly help activity recognition. This thesis performs evaluation of four different features for carried object detection. To detect carried objects, image chips in a video are extracted by tracking moving objects using an off the shelf tracker. Pixels with similar colors are grouped together by using a superpixel segmentation algorithm. Features are calculated with respect to every superpixel, encoding information regarding their location in the track chip, shape of the superpixel, pose of the person in the track chip, and appearance of the superpixel. ROC curves are used for analyzing the detection of a superpixel as a carried object using these features individually or in a combination. These ROC curves show that the detection using Shape features as they are calculated have very less information. The location features, though simple to calculate, have a significant usable information. Detection using pose of a person in the track chip and appearance of the superpixel depend largely on the data used for their calculation. Pose detections are more likely to be correct if there are no occlusions, while appearance work better if we have high resolution of input images.
Keywords: carried object detection; computer vision; image processing; machine learning; performance evaluation of features; video surveillance